2019
DOI: 10.1001/jamapsychiatry.2019.0876
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine Treatment Divide by Race/Ethnicity and Payment

Abstract: Opioid mortality rates continue to increase throughout the United States 1 ; however, growth in buprenorphine hydrochloride treatment for opioid use disorder (OUD) might be limited to communities with higher income and low percentages of racial/ethnic minorities. 2 Buprenorphine, a partial opioid agonist, is 1 of 3 evidence-based medications for treating OUD and can legally be prescribed in office-based settings. To our knowledge, no national studies have examined the differences in the receipt of buprenorphin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
258
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(274 citation statements)
references
References 5 publications
14
258
2
Order By: Relevance
“…They concluded that African American patients had statistically significantly lower odds of receiving buprenorphine prescription at their scheduled office visits (adjusted odds ratio, 0.23; 95% confidence interval, 0.13-0.44). 16 Similar findings of disparities were also reported by Hansen et al 17 and Marsh. 18…”
Section: Health Disparity and Racesupporting
confidence: 83%
“…They concluded that African American patients had statistically significantly lower odds of receiving buprenorphine prescription at their scheduled office visits (adjusted odds ratio, 0.23; 95% confidence interval, 0.13-0.44). 16 Similar findings of disparities were also reported by Hansen et al 17 and Marsh. 18…”
Section: Health Disparity and Racesupporting
confidence: 83%
“…In recent years, the burden of the opioid overdose crisis has disproportionately increased among blacks compared with whites [2]. Yet blacks receiving chronic prescription opioid treatment are more likely than whites to experience dose tapers [173], buprenorphine treatment remains largely concentrated among whites and in areas with higher proportions of white residents [174,175], and blacks who are able to access treatment are less likely to be successfully retained in care [146].…”
Section: Considerations For Health Disparity Populationsmentioning
confidence: 99%
“…In this context, DEI efforts are crucial in understanding how racial and ethnic URM groups are systematically excluded from the existing treatment options, and what changes can be made to repair the lack of attention given to URM communities deserving culturally affirming addiction treatment. Lagisetty 12 demonstrated that those who accessed MOUD were limited to individuals with higher income and in predominantly White communities. Racial and ethnic URM communities with OUD continue to be excluded from evidenced‐based treatments, despite having access to care through health insurance 12 .…”
Section: Dei and Health Outcomes: Deconstructing Gaps In Addiction Trmentioning
confidence: 99%
“…Lagisetty 12 demonstrated that those who accessed MOUD were limited to individuals with higher income and in predominantly White communities. Racial and ethnic URM communities with OUD continue to be excluded from evidenced‐based treatments, despite having access to care through health insurance 12 . This draws attention to a greater question of why racial and ethnic URM groups are not being adequately served by the existing addiction treatment system.…”
Section: Dei and Health Outcomes: Deconstructing Gaps In Addiction Trmentioning
confidence: 99%